“If doubt it ye cannot, then play unto its riddle the oedipus”: phillhelenic patterns in Edgar Allan Poe's tales - Tsokanos, Dimitrios (The Grove - Working Papers on English Studies, 2016)
Edgar Allan Poe's bicentenary triggered the interest of multiple scholars and academics and a number of researches based on Poe's works and their impact outside the United States have been produced. Quite astonishingly, even in Lois Vine's Poe Abroad (1999), a meticulous investigation upon the latter matter, Greece is nowhere to be mentioned. Apart from scarce mentions on Poe's influence by and on the Greek realm so far, the presence of Greek motifs in the American author's works has merely been delved into up to date. This paper aims to analyze this particular topic through Poe's Eleonora and Ligeia and it will attempt to demonstrate the philhellenic patterns existing in the literary idol's masterpieces along with the reasons why he turned to Greece as a source of inspiration.